Using 10Be dating to determine when the Cordilleran Ice Sheet stopped flowing over the Canadian Rocky Mountains. (July 2021) - Dulfer, Helen E.; Margold, Martin; Engel, Zbynĕk; Braucher, Régis; Team, Aster
Abstract: During the last glacial maximum the Cordilleran and Laurentide ice sheets coalesced east of the Rocky Mountains and geomorphological evidence indicates ice flowed over the main ridge of the Rocky Mountains between ~54–56°N. However, this ice flow has thus far remained unconstrained in time. Here we use in situ produced cosmogenic 10 Be dating to determine when Cordilleran ice stopped flowing over the mountain range. We dated eight samples from two sites: one on the western side (Mount Morfee) and one on the eastern side (Mount Spieker) of the Rocky Mountains. At Mount Spieker, one sample is rejected as an outlier and the remaining three give an apparent weighted mean exposure age of 15.6 ± 0.6 ka. The four samples at Mount Morfee are well clustered in time and give an apparent weighted mean exposure age of 12.2 ± 0.4 ka. These ages indicate that Mount Spieker became ice free before the Bølling warming and that the western front of the Rocky Mountains (Mount Morfee) remained in contact with the Cordilleran Ice Sheet until the Younger Dryas.